2004
DOI: 10.1111/j.0300-9475.2004.01507.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Adherence of Osteoarthritis and Rheumatoid Arthritis Synovial Fibroblasts to Cartilage and Bone Matrix Proteins and its Implication for Osteoarthritis Pathogenesis

Abstract: In osteoarthritis (OA), cartilage and bone fragments have been described within the synovial tissue which are surrounded by synovial cells (i.e. detritus synovitis). These cells appear to attach actively to the cartilage and bone fragments. In rheumatoid arthritis (RA), on the other hand, synovial fibroblasts (SF) have also been shown to be localized at sites of invasion into cartilage and bone and to degrade extracellular matrix (ECM) by secreting proteolytic enzymes. One prerequisite for exerting their aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Furthermore, the ability of recombinant maspin to inhibit the invasive process of these cells could be abrogated with a blocking antibody to the a5b1 integrin, which diminished the ability of cells to invade through a fibronectin matrixcontaining barrier in vitro, 21 supporting the idea that maspin alters the integrin profile rendering cells more adhesive, but less invasive. 21 As increased expression of integrins containing a5 and b1 has been described in RA synovial tissue, 22 23 and as RA SF could be shown to be less adhesive to collagen and other extracellular matrix components than OA SF, 24 these properties of RA SF might be due to the down regulation of maspin seen in the present study.…”
Section: Discussionmentioning
confidence: 51%
“…Furthermore, the ability of recombinant maspin to inhibit the invasive process of these cells could be abrogated with a blocking antibody to the a5b1 integrin, which diminished the ability of cells to invade through a fibronectin matrixcontaining barrier in vitro, 21 supporting the idea that maspin alters the integrin profile rendering cells more adhesive, but less invasive. 21 As increased expression of integrins containing a5 and b1 has been described in RA synovial tissue, 22 23 and as RA SF could be shown to be less adhesive to collagen and other extracellular matrix components than OA SF, 24 these properties of RA SF might be due to the down regulation of maspin seen in the present study.…”
Section: Discussionmentioning
confidence: 51%
“…In addition to integrins, transmembrane heparan sulfate proteoglycans of the syndecan family are involved in the attachment of cells to matrix components and there is evidence for a specific contribution of syndecan-4 in the activation of SFs 8. Nonetheless, the relevance of individual adhesion molecules as well as their specific binding partners in healthy and diseased cartilage has not been clarified, and recent data9 have complicated the picture by showing no significant differences in the overall attachment behaviour between RA SFs and osteoarthritis SFs.…”
Section: Introductionmentioning
confidence: 99%
“…A study on OSAD in rat primarily showed expression in bone marrow and in bone directly under articular cartilage forming in the femoral head (Shen et al, 1999). Furthermore, CHAD was recently demonstrated to promote rapid spreading of synovial fibroblasts from osteoarthritis (OA) patients, implicating a role in OA pathology (Schedel et al, 2004). …”
Section: Introductionmentioning
confidence: 99%